2021
DOI: 10.1016/j.ijcha.2020.100690
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of SGLT2 inhibitors compared to placebo in patients with heart failure: A systematic review and meta-analysis

Abstract: Background Heart failure (HF) prognosis without therapy is poor, however introduction of a range of drugs has improved it. We aimed to perform a systematic review on the effects and safety of sodium-glucose transporter 2 inhibitors (SGLT2i) in HF patients. Methods We carried out a systematic review of randomized controlled trials (RCTs) on SGLT2i compared to placebo for HF patients. We searched in PubMed, Scopus, Web of Science and EMBASE, with no language restriction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 72 publications
3
26
0
4
Order By: Relevance
“…Hence, our results provided more robust and comprehensive evidence for evaluating the effect of empagliflozin on HF. We observed significant improvements in heart failure hospitalizations and cardiovascular deaths, which is in line with a previous study ( 32 ) focused on the effect of SGLT2i in heart failure patients. However, regarding the two outcomes of a composite of cardiovascular death or hospitalization for worsening heart failure and hospitalization for worsening heart failure, our study showed greater RR reduction than the previous meta-analysis ( 32 ), which may indicate that empagliflozin is superior in patients with reduced ejection fraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, our results provided more robust and comprehensive evidence for evaluating the effect of empagliflozin on HF. We observed significant improvements in heart failure hospitalizations and cardiovascular deaths, which is in line with a previous study ( 32 ) focused on the effect of SGLT2i in heart failure patients. However, regarding the two outcomes of a composite of cardiovascular death or hospitalization for worsening heart failure and hospitalization for worsening heart failure, our study showed greater RR reduction than the previous meta-analysis ( 32 ), which may indicate that empagliflozin is superior in patients with reduced ejection fraction.…”
Section: Discussionsupporting
confidence: 92%
“…We observed significant improvements in heart failure hospitalizations and cardiovascular deaths, which is in line with a previous study ( 32 ) focused on the effect of SGLT2i in heart failure patients. However, regarding the two outcomes of a composite of cardiovascular death or hospitalization for worsening heart failure and hospitalization for worsening heart failure, our study showed greater RR reduction than the previous meta-analysis ( 32 ), which may indicate that empagliflozin is superior in patients with reduced ejection fraction. It is also worth noting that the results of our study and a previous trial with dapagliflozin intervention ( 33 ) demonstrated no significant difference in the change in NT-proBNP.…”
Section: Discussionsupporting
confidence: 92%
“…The most distinctive difference between our meta-analysis and other recent ones ( 63 , 64 ) is that this is the first meta-analysis investigating all current RCTs on SGLT2 inhibitors on HF with clinical endpoints, irrespective of the size of the trial. Furthermore, we included all available data of post-hoc analyses from large trials to elaborate the safety and efficacy of SGLT2 inhibitors in patients with established HF at baseline, irrespective of their diabetes status.…”
Section: Strengths Of This Meta-analysis and Differences As Compared To Other Meta-analysesmentioning
confidence: 92%
“… Among the binary secondary end points the statistically significant ones were KCCQ OS increase ≥ 5 points at 6 weeks, KCCQ CS increase ≥ 5 points at 12 weeks, NT pro-BNP decrease ≥20% at 12 weeks, BNP decrease ≥20% at 12 weeks. Among the continuous secondary end points the mean adjusted BNP at 12 weeks, mean adjusted KCCQ OS at 12 weeks, mean adjusted KCCQ CS at 12 weeks, mean adjusted HbA1c at 6 weeks were statistically significant IDDIA (2020) 26 60 Randomized, double-blind, placebo-controlled trial Follow up 24 weeks Patients with T2DM and HbA1c of 7.0% to 10.0% accompanied by LV diastolic dysfunction at least grade 1 (relaxation abnormality) on resting echocardiography Primary end point: Change is LV diastolic reserve at 24 weeks from baseline as assessed by diastolic stress echocardiography Secondary end points: Changes at 24 weeks in LV diastolic parameters at rest and during exercise, LV mass index, and left atrial volume index The patients in dapagliflozin group had significantly improved DR25W (0.88±1.24 cm/s versus −0.52±1.53 cm/s; P = 0.001) and DR50W (0.59±1.47 cm/s versus −0.58±1.63 cm/s; P = 0.035) compared with those in the placebo group at 24 weeks. Abbreviations: DAPA-HF, Study to Evaluate the Effect of Dapagliflozin on the Incidence of Worsening Heart Failure or Cardiovascular Death in Patients With Chronic Heart Failure; DECLARE-TIMI 58, Dapagliflozin and Cardiovascular Outcomes in Type 2 Diabetes; DEFINE-HF, Dapagliflozin Effect on Symptoms and Biomarkers in Patients With Heart Failure With Reduced Ejection Fraction; IDDIA, Randomized, Controlled Trial to Evaluate the Effect of Dapagliflozin on Left Ventricular Diastolic Function in Patients With Type 2 Diabetes Mellitus; HFrEF, Heart failure with reduced ejection fraction; NYHA, New York Heart Association; LVEF, left ventricular ejection fraction; NT-proBNP, N-terminal pro b-type natriuretic peptide; eGFR, estimated glomerular filtration rate; CKD-EPI, Chronic Kidney Disease Epidemiology Collaboration; GDMT, guideline-directed medical therapy; MACE, major adverse cardiovascular events; T2DM, Type 2 Diabetes Mellitus; HF, heart failure; KCCQ, Kansas City Cardiomyopathy Questionnaire; KCCQ-OS, Kansas City Cardiomyopathy Questionnaire Overall Summary Score; HbA1c, Glycated hemoglobin; KCCQ CS, Kansas City Cardiomyopathy Questionnaire Clinical Summary Score; BNP, B-type natriuretic peptide; LV, left ventricular; DR25W, Diastolic reserve at 25 Watts; DR50W, Diastolic reserve at 50 Watts.…”
Section: Existing Literature On Role Of Dapagliflozin In Cardiorenal Diseasementioning
confidence: 97%